Determinants of entrepreneurial intention among students : a study based on Asian Institute of Technology - Lopa, Nusrat Zahan; Vimolwan Yukongdi; Sununta Siengthai; Supasith Chonglerttham; His Majesty the King's Scholarship (Pathum Thani, Thailand : Asian Institute of Technology, 2016)
The main objective of the study was to identify the determinants of entrepreneurial intention among students. This study also aims to determine whether personal factors or situational factors have more influence em entrepreneurial intention. Personal factors include need for achievement, locus of control, risk taking, autonomy and authority while situational factors are challenges and opportunlties, job security, environment for starting business and education. Hence, a total of eight independent variables were tested for their effect on entrepreneurial intention. The study was conducted on the students of Asian Institute of Technology which is a renowned international educational institution in South-East Asia.Data was collected from the students of all schools and all programs through questionnaire survey. Nine hypotheses were tested using correlation analysis and multiple regression analysis. Among eight variables, five variables- need for achievement, risk taking tendency, challenges and opportunities, environment for starting business and education were found to significantly affect entrepreneurial intention. According to the result, both personal and situational factors significantly influence entrepreneurial intention of students, but personal factors tend to exert a greater degree of influence than do situational factors in this regard. Students have negative attitude towards situational factors especially environment for starting business and education.
A research submitted in partial fulfillment of the requirements for the degree of Master of Business Administration
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2016
Keywords: Entrepreneurship -- Education